2018
DOI: 10.1111/xen.12390
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genetically modified GTKO/hCD46/HLA‐E/hβ2−mg porcine hearts are protected from complement activation and natural killer cell infiltration during ex vivo perfusion with human blood

Abstract: GTKO, hCD46, and HLA-E expression in porcine hearts reduced complement deposition, complement dependent injury, and myocardial NK cell infiltration during perfusion with human blood. This tested combination of genetic modifications may minimize damage from acute human-anti-pig rejection reactions and improve myocardial function after xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…More recently, GGTA1 knock-out pigs with hCD46 and HLA-E/human β2-microglobulin transgenes were produced. The study showed that multiple genetically modified porcine hearts were protected from complement activation and myocardial natural killer cell infiltration in an ex vivo perfusion model with human blood [86]. Another approach to inhibit direct xenogeneic NK cytotoxicity is the elimination of porcine UL-16-binding protein 1 (ULBP1), which binds to NKG2D activating NK receptors.…”
Section: Cellular Xenograft Rejectionmentioning
confidence: 99%
“…More recently, GGTA1 knock-out pigs with hCD46 and HLA-E/human β2-microglobulin transgenes were produced. The study showed that multiple genetically modified porcine hearts were protected from complement activation and myocardial natural killer cell infiltration in an ex vivo perfusion model with human blood [86]. Another approach to inhibit direct xenogeneic NK cytotoxicity is the elimination of porcine UL-16-binding protein 1 (ULBP1), which binds to NKG2D activating NK receptors.…”
Section: Cellular Xenograft Rejectionmentioning
confidence: 99%
“…Genetically engineered pigs with swine leukocyte antigen (SLA) class I knock‐out (SLA‐1 KO), or expression of a mutant human class II transactivator gene (CIITA‐DN), have been produced to reduce pig antigen expression, and thus reduce the recipient's immune response, but are not yet being used consistently in experiments in NHPs. Pigs with transgenic expression of human HLA‐E/β2m and CD178 (FasL) have been produced to inhibit NK cell cytotoxicity, while the transgenic human CD47 gene contributes to regulate macrophage activation and phagocytosis . In addition, transgenic human CTLA4‐Ig (CD152) and CD253 (TRAIL) expression interrupt T‐cell activation and induce T‐cell apoptosis, respectively.…”
Section: Genetic Modification Of the Organ‐source Pigmentioning
confidence: 99%
“…In support of their hypothesis, expression of PD‐L1 significantly reduced human immune cell proliferation and improved cell survival. Similarly, Abicht et al genetically engineered pigs for hearts expressing combinations of transgenes. Using an ex vivo model in human blood, they demonstrate how the human immune system might respond to a porcine donor graft.…”
Section: Basic Researchmentioning
confidence: 99%